2012
DOI: 10.1186/1477-7819-10-67
|View full text |Cite
|
Sign up to set email alerts
|

Factors predictive of papillary thyroid micro-carcinoma with bilateral involvement and central lymph node metastasis: a retrospective study

Abstract: BackgroundThe optimal resection extent for papillary thyroid microcarcinoma (PTMC) remains controversial. The objective of the study was to investigate risk factors of bilateral PTMC and central lymph node metastasis (CLNM) to guide surgical strategies for PTMC patients.MethodsWe retrospectively reviewed 211 PTMC patients who underwent total thyroidectomy (TT) and 122 clinical lymph node-negative (cN0) cases that underwent prophylactic central lymph node dissection (CLND) between 2010 and 2011. The frequency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
3
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 32 publications
5
47
3
7
Order By: Relevance
“…Several studies reported that the presence of clinical lymph node metastasis in PTMC was one of the most important prognostic indicators, whereas others demonstrated that pathological lymph node metastasis identified following prophylactic dissection did not significantly affect patient prognosis. Pathological lymph node metastasis from PTMC was found in a range of 26-56% (15)(16)(17)(18)(19)(20). The reason(s) for the difference between clinical and pathological lymph node metastasis have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that the presence of clinical lymph node metastasis in PTMC was one of the most important prognostic indicators, whereas others demonstrated that pathological lymph node metastasis identified following prophylactic dissection did not significantly affect patient prognosis. Pathological lymph node metastasis from PTMC was found in a range of 26-56% (15)(16)(17)(18)(19)(20). The reason(s) for the difference between clinical and pathological lymph node metastasis have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Extrathyroidal extension and lymph node metastasis have been shown to be important predictors of locoregional recurrence in PTMC. 56,57 In some studies, 58-60 extrathyroidal extension has been reported in up to 52% of PTMCs. In our experience, extrathyroidal extension was seen relatively more commonly in microcarcinoma located at the periphery, involving the pseudocapsule of the thyroid gland.…”
Section: Pathologic Featuresmentioning
confidence: 99%
“…In our experience, extrathyroidal extension was seen relatively more commonly in microcarcinoma located at the periphery, involving the pseudocapsule of the thyroid gland. Niemeier et al 61 56 …”
Section: Pathologic Featuresmentioning
confidence: 99%
“…По данным литерату-ры, метастатическое поражение лимфоузлов было выявлено в 25-30% случаев [34,[43][44][45][46][47][48].…”
Section: микрокарциномы с метастатическим поражением лимфоузловunclassified
“…Несколько исследователей сообщили, что наличие метастазов в лимфатические узлы при микрокар-циномах является одним из наиболее важных про-гностических факторов, тогда как другие считают, что поражение лимфатических узлов существенно не влияет на прогноз пациента. Метастатическое пора-жение лимфоузлов при микрокарциномах было вы-явлено в 26-56% случаев [43][44][45][46][47][48].…”
Section: агрессивное лечение микрокарцином или их агрессивное течение?unclassified